HEPATITIS B VIRUS INFECTION AND ASSOCIATED FACTORS AMONG BLOOD DONORS IN ETHIOPIA: A CROSS-SECTIONAL STUDY - Sheik, Abdifetah Abdulahi; Getnet, Fental; Aden, Mowlid Akil; Yusuf, Abdulahi Mohamud; Dhicis, Ahmeddahir Abdi (Journal of Public Health Research and Community Health Development, 2024)
Background: Blood transfusion is a mandatory therapeutic maneuver that provides life-saving benefits to patients who are suffering from severe anemia due to medical disorders. Purpose: this study was aimed to determine HBV infection and associated factors among blood donars in Jigjiga zone Somali region. Methods: A facility-based cross-sectional study design was conducted among a sample blood donor in Jigjiga city Blood Bank Somali regional state of Ethiopia. A standardized questionnaire using Epidata was used. A bivariate and multivariate logistic regression was used to assess the independent predictors association (pvalue<0.25) in bivariate as candidate of multivariable logistic regression model-A significant (pvalue<0.05) was considered as statistical significance. Results: A total of 323 blood donars participated with a response rate of 95.5%. The overall prevalence of hepatitis B virus infection was (7.1%) (95% CI: 4.3-10.2)After adjusted analysis, marital status being single (AOR=5.3 CI: 1.018-27.859), unsafe therapeutic drug injections (AOR=10.1 CI: 2.791-36.566) unprotected sex (AOR4.6=CI: 1.533-14.116), razor and sharp material sharing (AOR=5.5 CI: 0.852-16.530), having poor knowledge on hepatitis B virus infection (AOR=3.4 CI: 1.107-10.485) were identified as statistically significant associated with hepatitis virus infection. Conclusion: Overall prevalence of the study was 7.1%, which needs intervention by the government and other stakeholders.